The Effectiveness of Telegram App in Learning English - Mana Alahmad (BIRCU, 2020)
There have been enormous improvements in every field in the modernized and technological period. When human understanding advances, several new developments have come to light and Such innovations contribute to human development. Because of the emergence of this modern technology and internet, the field of education is evolving a lot. The usual, blackboard books are replaced by smart boards and e-books. In addition, there is a behavioral shift in the learning of the learners and they rely more on modern technologies. Education, rather than teacher dependence. While teaching English, the teachers bring the new technology into their classrooms using the technology available, they change their methods and techniques to teach the EFL/ESL learners English. In their EFL / ESL classrooms even some teachers encourage the learners to use mobile phones to make their learning simple. This paper focuses on the studies done on the use of mobile phones in the classrooms. Moreover, the pros of using mobile apps for the learners are discussed.